PENGGUNAAN SEKAM PADI SEBAGAI MEDIA ALTERNATIF DAN PENGUJIAN EFEKTIFITAS PENGGUNAAN MEDIA PUPUK DAUN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT SECARA HIDROPONIK - Mardhiah Hayati (Jurnal Floratek, 2006)
The Aplication of PaddyHusks As An Alternative  Medium and  Test of Efectivity Of Foliar Fertilizer on Growth and Yield of Tomato In Hydroponics ABSTRACT             A research of using various media and fertilizers on tomato planted hydroponically has been conducted in the green house of Agriculture faculty, Syiah Kuala University, Banda Aceh, starting from July to November 2002. The objective of research was to observe the influence of various media and fertilizer, as well as the interaction of each other to the growth and yield of tomato planted hydroponically. The treatment composed of two factors, namely various media (paddy’s husks / kuntan, sands, and mixture of  kuntan and sands) and fertilizers (Vitamon, Bayfolan, Complesal and Hoagland solution). The research was assigned in completely randomized design in a factorial manner, consisting three replications. The results showed that the best growth and highest yield of the tomato were found in the mixture medium (kuntan + sands). These results were significantly different from those of the single medium. The use of Hoagland solution resulted on the best growth and highest yield of tomato which were not significantly different from those of Bayfolan and Complesal Fertilizer. It is observed that there were no significant interactions between the two factors tested.